Integrative omics and experimental validation reveal METTL17 and SLC27A1 as biomarkers and potential therapeutic targets in chronic kidney disease - Ling, Shiyun; Xie, Kaifeng; Chen, Penghui; Liang, Lichang; Shi, Xinyu; Huang, Renfa (Frontiers in Immunology, 2026)
BackgroundChronic kidney disease (CKD) remains a global health challenge characterized by high morbidity and mortality, yet its molecular mechanisms remain incompletely defined. Both mitochondrial dysfunction and macrophage polarization have been implicated in CKD pathogenesis, but the precise gene networks and cellular contexts driving these processes are poorly understood.MethodsAn integrative analysis of bulk RNA sequencing, single-cell transcriptomics, and clinical validation was performed to identify key genes linking mitochondrial regulation and macrophage polarization in CKD. Differentially expressed genes were intersected with mitochondria- and macrophage-related gene sets, refined by machine learning, and assessed through functional enrichment, immune infiltration, and network analyses. Single-cell RNA-seq was applied to resolve cellular heterogeneity and ligand–receptor interactions, while experimental validation was carried out in CKD patient peripheral blood samples and a unilateral ureteral obstruction (UUO) mouse model using qPCR, immunohistochemistry, and Western blotting.ResultsA total of METTL17 and SLC27A1 were identified as consistently dysregulated genes across datasets, with METTL17 downregulated and SLC27A1 upregulated. Single-cell analysis localized these alterations primarily to proximal tubular cells (PTCs) and smooth muscle cells (SMCs), where ligand–receptor signaling mediated pathogenic intercellular communication. Immune infiltration analysis revealed selective alterations in naïve B cells, activated NK cells, and γδ T cells, highlighting crosstalk between metabolic and immune pathways. Importantly, both genes showed positive correlations with serum creatinine in CKD patients (e.g., SLC27A1: r = 0.467, P = 0.038), underscoring their clinical relevance. Experimental validation in CKD patient peripheral blood samples (P < 0.01 for both genes) and in a unilateral ureteral obstruction (UUO) mouse model of renal fibrosis confirmed consistent dysregulation: METTL17 was significantly downregulated and SLC27A1 upregulated at both mRNA and protein levels (e.g., immunohistochemistry, P < 0.05). These alterations were spatially localized to proximal tubules and coincided with marked collagen deposition.ConclusionThis study identifies METTL17 and SLC27A1 as key mediators of CKD progression, bridging mitochondrial dysfunction, metabolic reprogramming, and immune imbalance. These findings provide a translational framework for developing biomarker-driven diagnostics and targeted interventions in CKD.